Claire Legendre’s Portrait of Hypermodern Society - Michèle A. Schaal (Studies in 20th & 21st Century Literature, 2013)
Theorists from various academic disciplines believe Western society has entered an age of excess and exacerbated modernity: all areas of life are affected by a will to be or do more at an always faster pace. This article focuses on French writer Claire Legendre’s literary translation of hypermodernity, especially in her narratives published over the past decade. First, it examines her portrayal of contemporary individuality, marked by all sorts of excesses and especially by the imperative to make the most of oneself and one’s life. This ideal being in itself excessive, her characters resort to extreme behaviors. However, they never fully manage to achieve the uniqueness or exceptionality hypermodernity entails. Then, the article reveals how Legendre’s writing itself becomes hypermodern: she explores aesthetically some notions at stake in hypermodernity such as self-reflexivity, undecidability and intermediality. In her novels, they become literary techniques that question, among other things, autofiction or render any final interpretation of her narratives impossible. Finally, this study shows that, even if hypermodern ideals affect women and men alike, the former still remain subjected to discriminative gender politics. For Legendre, women still suffer from contradictory and sometimes exacerbated forms of physical or emotional violence.
Keywords: Claire Legendre; hypermodernity; contemporary individuality; hypermodern; self-reflexivity; decidability; uncertainty; intermediality; autofiction; discriminative gender politics; women